Violent Universe. High-energy astrophysics and cosmology in the twenty-first century - Manel Perucho Pla; José Antonio Font Roda (Mètode Science Studies Journal: Annual Review, 2021)
We see the sky and admire its regularity and stability, its apparent immutability. We have always done so; it does not come as a surprise, since humans have always been startled by any change in the sky, associating it with omens or the mood swings of gods. At that time, they might call these changes «new stars», even if they were, for example, a supernova explosion, as in the case of Tycho’s supernova in the sixteenth century.